Modelling the inactivation and possible regrowth of Salmonella enterica treated with chlorophyllin-chitosan complex and visible light - Rodríguez-López, María Isabel (Array, 2020)
The study focuses on predictive modelling of inactivation of Salmonella enterica after treatment with chlorophyllin-chitosan complex and visible light. Salmonella cells were incubated with chlorophyllin-chitosan complex (0.001 % chlorophyllin and 0.1 % chitosan) for different times (5-60 min) and then illuminated with visible light (λ=405 nm, He=38 J/cm2). Inactivation curves and post-treatment regrowth curves were built based on microbiological viability tests and data were fitted to ten inactivation and two regrowth models. The photoactivated complex reduced Salmonella population, which were unable to regrow. Weibull and Baranyi models were the best to describe the inactivation and regrowth kinetics respectively. In conclusion, data from the kinetic analysis and predictive modelling confirmed that photoactivated chlorophyllin-chitosan complex is a promising non-thermal approach for inactivation of Gram-negative pathogens, since no bacterial regrowth after treatment has been predicted.